Impact of Biological and Chemical Seed Treatments on Wilt of Castor (Ricinus communis L.) Caused by Fusarium oxysporum f. sp. ricini - Chandini, A.; Prasad, R. D.; Sakthivel, K.; Duraimurugan, P.; Chandrika, K. S. V. P.; Sarada, Ch.; Suresh, M. (International Journal of Economic Plants, 2025)
The experiment was conducted during January, 2024-March, 2025 at ICAR-IIOR, plant pathology unit to study the impact of various biological and chemical treatments on controlling the most important wilt disease caused by Fusarium oxysporum f. sp. ricini in castor crop. The biocontrol agent Trichoderma harzianum, Th4d strain and castor wilt virulent pathogen, Fusarium oxysporum f. sp. ricini were sourced from the ICAR-IIOR Pathology Unit. The impact of chemical and biological seed treatments i.e., Vitavax (carboxin 37.5%+thiram 37.5% WS at 3.0 g kg-1), T. harzianum Triguard Th-WP (Th4d 1.5% WP at 10.0 g kg-1) and Evergol xtend (penflufen 13.28% w/w+trifloxystrobin 13.28% w/w FS at 1.0 ml kg-1) against castor wilt through poisoned food technique under in vitro and pot culture study under in vivo conditions. Among the different treatments tested, Th4d was effective in reducing disease incidence by 26.1% and 28.1% respectively under in vitro and in vivo conditions. The results suggest that seed treatment with chemical fungicides and the biological control agent can be effective in management of the wilt pathogens. The concerns over environmental impacts of chemicals, their toxicity and possibility of development pathogen resistance have led to a shift towards more sustainable solutions. In this context, the biological seed treatment with Trichoderma Th4d strain has emerged as a promising method for managing the wilt pathogen in castor.